2016
DOI: 10.1016/j.icheatmasstransfer.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical experiments of density driven CO2 saturated brine migration in heterogeneous two-dimensional geologic fabric materials

Abstract: CO 2 geological sequestration has been recognized as one of the potential solutions for reducing anthropogenic atmospheric emissions. To better estimate the storage efficiency (capacity) of subsurface geologic formations and to understand the plume migration mechanism through porous geologic formations, this study performs numerical simulations of density driven CO 2-saturated brine flow in highly resolved heterogeneous 2D fabrics. While large-scale convective currents driven by gravity have been cited as impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In the Fickian diffusion process, CO 2 diffuses into brine and forms a diffusive boundary layer 11 that grows in proportion to the square root of time (), where perturbations to the stable layer are damped. 5 The relationship curve between the mole number of CO 2 dissolved in resident brines ( n t ) and the root of time () is drawn in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Fickian diffusion process, CO 2 diffuses into brine and forms a diffusive boundary layer 11 that grows in proportion to the square root of time (), where perturbations to the stable layer are damped. 5 The relationship curve between the mole number of CO 2 dissolved in resident brines ( n t ) and the root of time () is drawn in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 The molecular diffusion of CO 2 in brine is woefully slow. 5 The key issue for accurate assessment of the dissolution trapping is the dissolution rate. As illustrated in Figure 1, many mechanisms accelerate the diffusion of CO 2 in brine and involve dispersion, 6 advection, and gravitational convection.…”
Section: Introductionmentioning
confidence: 99%
“…The air density can be approximately taken as 1.225 kg/m 3 . This gives the content of CO2 in air is about 0.479 g/m3 . The maximum amount of CO2 that can be consumed in concrete carbonation can be estimated as follows[33], CaO (≈0.64) is the amount of calcium oxide per weight of cement, Cem is the content of cement used in concrete, MCO2=44 g/mol and MCaO=56 g/mol are the molar weight of CO2…”
mentioning
confidence: 94%
“…Two major causes that are connected to corrosion of reinforcing steel in concrete structures are the carbonation and chloride attack. Carbonation is a set of reactions between atmospheric carbon-dioxide and alkaline components of concrete, producing a carbonated surface layer in which the pore solution pH value is depressed to nearneutral levels [1,2,3]. A secondary effect of carbonation, also significant in terms of its influence on reinforcing steel corrosion, is that it can cause the release of bound chloride ions into the pore solution phase of concrete that contains a modest level of chloride salts as a contaminant, thus exacerbating the corrosive nature of the electrolyte [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kong and Saar (Kong and Saar, 2013) investigated the effect of stochastic heterogeneity on DDC processes during the dissolution of CO2 in brine. Based on numerical experiments, Islam et al (2016b) showed that DDC and dissolution processes are influenced primarily by the heterogeneity in grain size. Dai et al (2018) investigated the effectiveness of the heterogeneity-induced trapping mechanism.…”
Section: Introductionmentioning
confidence: 99%